Vocal performance is a salient signal for male–male competition in White-crowned Sparrows. (10th May 2017) - Phillips, Jennifer N.; Derryberry, Elizabeth P.
Abstract: Vocal communication in songbirds is important for aggressive signaling, such that an honest signal allows receivers to assess a competitor's qualities. One aspect of song that conspecifics may assess is vocal performance. An example of vocal performance is how well an individual performs the trade-off between trill rate and bandwidth in production of repeated notes. This type of vocal performance (vocal deviation) is thought to be an honest signal because a male's ability to maximize both bandwidth and trill rate is limited by motor constraints on sound modification. Further, how well a male can repeat this trade-off may provide receivers with information about the signaler, and a male's own level of vocal performance can affect the strength of response to high-performance songs. We tested whether males assess each other based on vocal performance in an important model species, the White-crowned Sparrow ( Zonotrichia leucophrys ). We show that male White-crowned Sparrows respond more strongly to high-performance songs than to lower-performance songs in 2 different locations, supporting the hypothesis that males utilize vocal performance to assess competitors. We also provide initial evidence that vocal performance varies among males and is repeatable within individuals.